Neonatal respiratory distress: recent progress in understanding pathogenesis and treatment outcomes - So Young Kim (Korean Pediatric Society, 2010)
Transient tachypnea of the newborn (TTN), respiratory distress syndrome (RDS), and persistent pulmonary hypertension (PPHN) are the three most common disorders that cause respiratory distress after birth. An understanding of the pathophysiology of these disorders and the development of effective therapeutic strategies is required to control these conditions. Here, we review recent papers on the pathogenesis and treatment of neonatal respiratory disease.